2016
DOI: 10.1038/srep35694
|View full text |Cite
|
Sign up to set email alerts
|

Current driven transition from Abrikosov-Josephson to Josephson-like vortex in mesoscopic lateral S/S’/S superconducting weak links

Abstract: Vortices are topological defects accounting for many important effects in superconductivity, superfluidity, and magnetism. Here we address the stability of a small number of such excitations driven by strong external forces. We focus on Abrikosov-Josephson vortex that appears in lateral superconducting S/S’/S weak links with suppressed superconductivity in S’. In such a system the vortex is nucleated and confined in the narrow S’ region by means of a small magnetic field and moves under the effect of a force p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
0
25
1
Order By: Relevance
“…For instance, radiation by AJ vortices can be enhanced as they move in a periodic magnetic potential of A vortices along grain boundaries 28,55 , whereas A vortices trapped perpendicular to the junction can result in generation of V-AV pairs in the presence of the applied electric current 56 . The result of this work may also pertain to the transition of A vortices driven by strong currents into chains of weakly coupled J vortices or phase slips in wide thin films [57][58][59][60][61][62][63] . In this case vortices moving along a self-induced channel of reduced order parameter behave as overdamped AJ vortices considered here.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, radiation by AJ vortices can be enhanced as they move in a periodic magnetic potential of A vortices along grain boundaries 28,55 , whereas A vortices trapped perpendicular to the junction can result in generation of V-AV pairs in the presence of the applied electric current 56 . The result of this work may also pertain to the transition of A vortices driven by strong currents into chains of weakly coupled J vortices or phase slips in wide thin films [57][58][59][60][61][62][63] . In this case vortices moving along a self-induced channel of reduced order parameter behave as overdamped AJ vortices considered here.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, it has been shown that many different kinds of superconducting states can exist in mesoscopic samples [2,[5][6][7][8][9][10][11]. Vortices also show very rich static and dynamic behavior in the presence of a weak link [7,10,14]. It is well known properties of both superconducting and normal metals are modified due to the proximity effect [15] when they are in contact with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies have shown that vortex-antivortex states can also be stabilized in submicron superconductors even in a homogeneous magnetic field [17]. Vortices show very rich static and dynamic behavior in the presence of a weak link [9,12,18]. A weak link is commonly achieved by two superconducting layers separated by a normal metallic layer, or a weak superconducting region.…”
Section: Introductionmentioning
confidence: 99%
“…Since recently, such superconducting samples (cylindrical wires and tubes) were experimentally realized [22]. In this paper, we investigate the 3D time-dependent Ginzburg-Landau (TDGL) equations in the order parameter ψ of the Cooper-pair condensate for fully 3D cylindrical samples in the basis of finite-element method (FEM) [12,23], which is proved to be an effective method for the mesoscopic superconductors with a complex geometry [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation